2012
DOI: 10.1111/j.1476-5381.2011.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐(1‐7) inhibits epidermal growth factor receptor transactivation via a Mas receptor‐dependent pathway

Abstract: BACKGROUND AND PURPOSEThe transactivation of the epidermal growth factor (EGF) receptor appears to be an important central transduction mechanism in mediating diabetes-induced vascular dysfunction. Angiotensin-(1-7) [Ang-(1-7)] via its Mas receptor can prevent the development of hyperglycaemia-induced cardiovascular complications. Here, we investigated whether Ang-(1-7) can inhibit hyperglycaemia-induced EGF receptor transactivation and its classical signalling via ERK1/2 and p38 MAPK in vivo and in vitro. EXP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 54 publications
9
93
0
Order By: Relevance
“…In proximal tubular cells, Ang II-stimulated phosphorylation of three MAP kinases (p38, ERK1/2 and c-Jun) was also inhibited by Ang-(1-7), an effect that was also completely blocked by the Mas antagonist A-779 (Su et al 2006). Furthermore, a Mas-dependent inhibition of Ang IIinduced EGFR transactivation by Ang-(1-7) has also been demonstrated in rat VSMCs (Akhtar et al 2012).…”
Section: Metabolic Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 59%
“…In proximal tubular cells, Ang II-stimulated phosphorylation of three MAP kinases (p38, ERK1/2 and c-Jun) was also inhibited by Ang-(1-7), an effect that was also completely blocked by the Mas antagonist A-779 (Su et al 2006). Furthermore, a Mas-dependent inhibition of Ang IIinduced EGFR transactivation by Ang-(1-7) has also been demonstrated in rat VSMCs (Akhtar et al 2012).…”
Section: Metabolic Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 59%
“…Prevention of diabetes-induced abnormal vascular responsiveness to noradrenaline, endothelin-1, AngII, carbachol and histamine in the mesenteric bed, isolated carotid and renal arteries [173]; increased LV-developed pressure and serum nitrite/nitrate and decreased LV mass/body mass and LV collagen content [174]; AVE-0991 rescued cardiac function under diabetic conditions as indicated by a normalization of blood pressure and contractility parameters [175]; and Ang-(1-7) inhibited EGF receptor transactivation via a Mas receptor/Src-dependent pathway, indicating that activation of the EGF receptor is a key player in mediating diabetes-induced vascular dysfunction [177] Chronic infusion of XNT (ACE2 activator) on STZ-induced diabetic rats Improved endothelium-dependent vasorelaxation of aortic rings; effect blocked by A-779 [176] Deletion of ACE2 in diabetic Akita mice…”
Section: Pathology Experimental Approach Effectmentioning
confidence: 97%
“…In general these studies imply a cardioprotective role for Ang-(1-7) under hyperglycaemic conditions and point to new therapeutic strategies using Ang-(1-7) agonists to treat the cardiovascular complications associated with diabetes mellitus. A potential mechanism involved in these beneficial effects of Ang-(1-7) could be related to its ability to inhibit EGF (epidermal growth factor) receptor transactivation via a Mas receptor-dependent pathway [177]. In addition, an indirect role for this cardioprotective role of Ang-(1-7) has been demonstrated by deletion of the Ace2 gene in diabetic Akita mice.These animals displayed increased plasma and tissue AngII, impaired systolic and diastolic function, and increased NADPH oxidase activity and greater oxidative stress in the heart [178].…”
Section: Pathology Experimental Approach Effectmentioning
confidence: 98%
“…Thus, targeting EGFR inhibition with MR antagonists such as RU may have beneficial and detrimental consequences in the heart and thus their net therapeutic advantage will depend on the relative importance or contributions of these different EGFR-driven mechanisms in a given pathological state. Indeed, we have recently shown that by removing the EGFR inhibitory effects of Los, which blocks Ang II-mediated transactivation of EGFR, by coadministering an EGFR ligand, significant improvement in cardiac function over that achieved by Los alone was attained [40]. …”
Section: Discussionmentioning
confidence: 99%